Peripheral oxygen saturation levels as a guide to avoid hyperoxia: an observational study - Renate Stolmeijer; Jan C. ter Maaten; Jack Ligtenberg; Ewoud ter Avest (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background As iatrogenic hyperoxia has been related to adverse outcomes in critically ill patients, guidelines advise to titrate oxygen to physiological levels. In the prehospital setting where partial arterial oxygen (PaO2) values are often not readily available, titration of oxygen is based on peripheral oxygen saturations (SpO2). In this study we aimed to investigate the efficacy of SpO2 guided oxygen titration in the prevention of hyperoxia. Methods In a retrospective observational cohort study of patients included in the Acutelines data- and biobank of the University Medical Center Groningen between September 2020 and March 2023, we collected blood gas samples and triage data of sequentially included patients who received oxygen at the moment they were presented in the emergency department (ED). PaO2 values were compared to (concurrently measured) SpO2 values, and to patient- and treatment characteristics and P/F ratios were calculated in order to investigate the efficacy of SpO2 based oxygen titration for various subgroups. Results Blood gas samples were obtained for 1042 patients, of which 178 (17.1%) had hyperoxia (PaO2 levels > 13.5 kPa). SpO2 readings were available for 170 of these, 68 of which (40%) had SpO2 values above the recommended target range (94–98%; 88–92% for patients with COPD) whereas 102 patients (60%) had SpO2 values within- or even below the recommended target range. Many of these patients (44.1%) received oxygen through a low-flow device (nasal canula), and these patients almost invariably (84.4%) were not compromised in their ventilation (P/F ratio’s > 300). Conclusion When oxygen is titrated based on SpO2 levels, this results in hyperoxemia in a significant proportion of the patients. Health care providers should especially be reluctant to administer (low flow) oxygen as a standard of care to patients who do not have clear respiratory compromise, as these patients are at a high risk of developing (occult) hyperoxia.